Controllable Patterning of Hybrid Silicon Nanowire and Nanohole Arrays by Laser Interference Lithography. Issue 6 (23rd March 2020) - Guo, Xudong; Li, Songhao; Lei, Zecheng; Liu, Ri; Li, Li; Wang, Lu; Dong, Litong; Peng, Kuiqing; Wang, Zuobin
Abstract : Metal‐assisted chemical etching (MACE) is a cost‐effective method to fabricate Si nanostructures including silicon nanowires (SiNWs) and silicon nanoholes (SiNHs). However, the preparation of metallic template for MACE would require complex experimental conditions including strict cleaning process and multiple steps. Herein, superlens‐enhanced laser interference lithography is applied to directly fabricate complicated metallic patterns and then MACE is used to obtain hybrid SiNW and SiNH arrays. Ag films are first deposited on Si substrates, and then a 1064 nm high power laser source is utilized to generate two‐beam interference electric fields. Because Ag molecules are very sensitive to any input energy change, they tend to break up or aggregate and form different Ag patterns which have a specific energy threshold to lower its free energy. By manipulating the distribution of input electric field, complicated metallic patterns and their corresponding Si nanostructures with feature sizes that range from tens of nanometers to several micrometers are obtained. Abstract : Hybrid silicon nanowire and nanohole arrays with different periods, surface area contrasts, directions, etching depths, densities, and sizes are controllably fabricated by metal‐assisted chemical etching of corresponding metallic patterns obtained by a one‐step lithography method. More complicated Si nanostructures are also fabricated, whose sizes vary from nano‐ to microscales in a narrow period.